Pharmacokinetics of butafosfan after intravenous and intramuscular administration in piglets. Issue 2 (31st July 2016) - Sun, F.; Wang, J.; Yang, S.; Zhang, S.; Shen, J.; Xingyuan, C.
Abstract : The pharmacokinetics and bioavailability of butafosfan in piglets were investigated following intravenous and intramuscular administration at a single dose of 10 mg/kg body weight. Plasma concentration–time data and relevant parameters were best described by noncompartmental analysis after intravenous and intramuscular injection. The data were analyzed through WinNolin 6.3 software. After intravenous administration, the mean pharmacokinetic parameters were determined as T 1/2 λ z of 3.30 h, Cl of 0.16 L kg/h, AUC of 64.49 ± 15.07 μg h/mL, V ss of 0.81 ± 0.44/kg, and MRT of 1.51 ± 0.27 h. Following intramuscular administration, the C max (28.11 μg/mL) was achieved at T max (0.31 h) with an absolute availability of 74.69%. Other major parameters including AUC and MRT were 48.29 ± 21.67 μg h/mL and 1.74 ± 0.29 h, respectively.